Prospective cohort study of ultrasound surveillance of regional lymph nodes in patients with intermediate‐risk cutaneous melanoma. Issue 6 (28th February 2019) - Hayes, A. J.; Moskovic, E.; O'Meara, K.; Smith, H. G.; Pope, R. J. E.; Larkin, J.; Thomas, J. M.
Abstract : Background: For patients with intermediate‐thickness melanoma, surveillance of regional lymph node basins by clinical examination alone has been reported to result in a larger number of lymph nodes involved by melanoma than if patients had initial sentinel node biopsy and completion dissection. This may result in worse regional control. A prospective study of both regular clinical examination and ultrasound surveillance was conducted to assess the effectiveness of these modalities. Methods: Between 2010 and 2014, patients with melanoma of thickness 1·2–3·5 mm who had under‐gone wide local excision but not sentinel node biopsy were recruited to a prospective observational study of regular clinical and ultrasound nodal surveillance. The primary endpoint was nodal burden within a dissected regional lymph node basin. Secondary endpoints included locoregional or distant relapse, progression‐free and overall survival. Results: Ninety patients were included in the study. After a median follow‐up of 52 months, ten patients had developed nodal relapse as first recurrence, four had locoregional disease outside of an anatomical nodal basin as the first site of relapse and six had relapse with distant disease. None of the patients who developed relapse within a nodal basin presented with unresectable nodal disease. The median number of involved lymph nodes in patients undergoing lymphadenectomy for nodal relapse was 1 (range 1–2; mean 1·2). Conclusion: This study suggests that ultrasound surveillance of regional lymph node basins is safe for patients with melanoma who undergo a policy of nodal surveillance. Abstract : There is ongoing debate regarding the optimal method of locoregional surveillance in patients with melanoma. In a prospective study, ultrasound surveillance and clinical examination was found to be a safe non‐invasive strategy of follow‐up. Patients who developed locoregional relapse had low nodal burdens and experienced minimal operative complications. Safe if sentinel node biopsy not needed